The Association of Encrustation and Ureteral Stent Indwelling Time in Urolithiasis and KUB Grading System - Kartal, Ibrahim Guven; Baylan, Burhan; Gok, Alper; Sagnak, Azmi Levent; Karakoyunlu, Nihat; Cakici, Mehmet Caglar; Kaymak, Serafettin; Karabacak, Osman Raif; Topaloglu, Hikmet; Ersoy, Hamit (Urology Journal, 2018)
Purpose: To evaluate the management of prolonged indwelling ureteral stents and the newly developed KUB (kidney, ureter, and bladder) grading system for the classification of encrusted stents in urolithiasis. Method: This study involved 69 patients that had indwelling and forgotten ureteral stents for more than 6 months after urolithiasis treatment. They were categorized into 4 groups based on indwelling time and were reviewed retrospectively. Patients whose ureteral stent could not be removed with simple cystoscopy were graded according to stone surface area and the KUB system. Results: The mean stent indwelling time was 23.1 months. Stone burden in KUB and, in proportion to that, total KUB (T) score showed increased association that was directly proportional to indwelling time (p < 0.001, p = 0.008). Surgical intervention was required in 73.9% of patients. Among patients requiring surgery, 78.4% were treated in a single session and multi-modal interventions were performed in 70.5%. K score ? 3 was found to be associated with multiple surgery requirements (odds ratio [OR];11.25, %95 confidence interval [CI]:2.132-59.375), multi-modal procedure requirements (OR;16.50, %95 CI:3.434-79.826 ), and lower stone-free rates (p = 0.04). B score ? 3 was associated with multi-modal procedure requirements (OR;8.90, %95 CI:1.052-75.462). U score ? 3 and T score ? 9 were associated with an operating time >180 minutes (p < 0.001, p = 0.008). Conclusion: Prolonged indwelling time of the ureteral stent in urolithiasis is associated with increased encrustation and stone burden. Since the KUB system specifies stone burden and its particular localization, it can be used as a simple, convenient method for the planning treatment of encrusted ureteral stents.